Neutrophil-lymphocyte Ratio and Platelet-lymphocyte Ratio as Early Sign Plasma Leakage Process in Dengue Infection - Ashma, Aisya Nailatul; Susilo, Satrio Budi; Marwanta, Sri; Harioputro, Dhani Redhono (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Dengue hemorrhagic fever remains a global health concern, especially in tropical and subtropical regions, such as Indonesia. Plasma leakage is the main symptom of Dengue infection which be seen through a hemoconcentration. NLR and PLR are cost-effective and easily measurable indexes that help to predict signs of infection. This study aims to analyze the correlation of NLR and PLR as early sign on hemoconcentration in Dengue infection. This study was an analytical observational method with a cross-sectional design. The study was conducted at the inpatient infectious disease wards of Dr. Moewardi General Hospital and Sebelas Maret University Hospital. The data was statistically analyzed using bivariate and multivariate analysis. There were seventy subject which of male was more than female. The result of bivariate analysis showed a statistically significant correlation for NLR (p = 0,008; r = 0,314) and non-significant for PLR (p = 0,150; r = 0,174). Both NLR and PLR were positively correlated with hemoconcentration. The effect of NLR on hemoconcentration was significant. There was a positive correlation significant between NLR and hemoconcentration in Dengue infection.